Performance is Assessed In Terms of Workload, Leadership, Competence and Training - Agung Purowoko; Istiatin Istiatin; Bambang Mursito (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to understand and explain the influence of workload, leadership, competence, and training on the performance of employees of the Criminal Investigation Unit of Surakarta Police Department. The population of this study is the Criminal Investigation Unit of Surakarta Police Department, consisting of 102 people, and the sample consists of 52 people using a simple proportion sampling technique. Data was collected using a questionnaire. The data analysis technique used the Multiple Linear Analysis method. The results of the study show that workload, leadership, competence, and training contribute 80.5% to performance, while the remaining 19.5% is explained by other variables not included in this study. The suggestion from this study is that the employees of the Criminal Investigation Unit of Surakarta City Police can improve their competence and training, as well as leadership, which is able to manage employee workloads to achieve optimal performance results for the Criminal Investigation Unit of Surakarta City Police.